Networks and network analysis for defence and security - a book review - Ferreira, Manuel Alberto M. (2014)
It is intended in this work to review the book"Networks and Network Analysis for Defence and Security", 978-3-319-04146-9 published in Springer Series “Lecture Notes in Social Networks”. In this book the following areas are covered: Defence and security risk analysis; Criminal intelligence; Cyber crime;Cognitive analysis; Counter-terrorism and Social Network Analysis; Transnational Crime; Critical infrastructure analysis; Support to defence and security intelligence, emphasizing the idea that network analysis is a “key enabler in supporting defence and security”.Not only man-made threats against nation’s security are considered but also the ones resulting from natural hazards. With the emergence and enormous progress in“big data” analysis together with innovative interpretative approaches, network analysis facilitates a greater understanding of complex networks: their entities, inter dependencies and vulnerabilities.